Utilization of Social Media for Writing Learning in Elementary School - Sanubari, Murni; Rahman (International Conference on Elementary Education, 2022)
The acceleration of technology in education has brought children so close to the digital world and social media. According to data, 87% of primary school age children in Indonesia use social media. This is a potential for social media to be used in learning in elementary schools, especially in writing skills. The low writing skill in elementary school makes this skill need attention and improvement. The Program for International Students Assessments (PISA) in 2015 showed that Indonesia was in position 64 out of 75 countries with low literacy. Social media is ideally used in learning to improve students' writing skills in elementary schools. This study aims to describe how the use of social media for learning to write in elementary schools. The method used is literature review by reading, studying, comparing, studying and drawing conclusions. Researchers found that social media can be used and utilized as learning media, study rooms, and communication facilities in improving writing skills in elementary schools, especially in high grades. Social media provides good benefits for learning to write in elementary school.